IMPLEMENTASI KESETARAAN GENDER DAN PEMBERDAYAAN WANITA DALAM PROSES REKRUTMEN KARYAWAN - Suryono Efendi (GoAcademica Research dan Publishing, 2020)
Globalization has given more varied employees the possibility of seeing diversity as a key component in empowerment. As the workplace evolves due to globalization, technology and diversity, corporate executives must proactively adapt these changes. Organizational leaders need to be strategically proactive to retain their organisations, not just to survive in an increasingly competitive market, competitive and prosperous on the long run. This paper explores how sex empowerment and equality may be used strategically for recruiting, promoting, retaining women and so helping to achieve organizational success.